After the great complacence financial crisis and the politics of reform - Engelen, Ewald (Oxford : Oxford University Press, 2011)
This text provides an accessible cultural and political analysis of how our disorderly and financialized system of capitalism works, what led to the financial crisis that began in 2007, the policy debates about reform, and why democratic control is difficult after the events of 2008.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Global Financial Crisis, 2008-2009.; Finance, Public -- History -- 21st century; Financial institutions -- Government policy; Financial services industry -- Law and legislation